Biodiversity revisited through systems thinking. (5th March 2021) - Davila, Federico; Plant, Roel; Jacobs, Brent
Summary: Systems thinking provides a comprehensive range of theories and methods that are useful for understanding and managing sustainability challenges. Biodiversity conservation is riddled with complex interactions between science, society and myriad interacting systems through temporal and spatial scales. This article presents a synthetic analysis of the history of systems thinking from a genealogical perspective, drawing from hard and soft systems thinking, and resilience and social-ecological systems. Using the anchor point of system leverage points and system characteristics (parameters, feedbacks, design and intent), we employ a diversity of examples to illustrate their relevance to multiple biodiversity related problems. We conclude by illustrating the opportunities for systems thinking to bridge epistemic divides with multiple biodiversity actors working towards conservation outcomes. Systems thinking can support more integrative biodiversity interventions, as they provide a pluralistic set of tools for bridging knowledges and disciplines, which can be useful to create new shared understandings of how to conserve biodiversity.